ANALISA PENERAPAN E-GOVERNMENT PADA PROGRAM KEMANDIRIAN KETAHANAN PANGAN DI LAPAS NARKOTIKA KELAS IIA KARANG INTAN - Muhammad Reza Arisandi; Meitisa Vanya Simanjuntak (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This study aims to analyze the implementation of e-government in the foodsecurity based self-reliance program at the Class IIA Narcotics CorrectionalInstitution of Karang Intan and to identify the supporting and inhibiting factorsthat influence its success. The research employs a descriptive qualitativeapproach, using in-depth interviews, participatory observation, and documentanalysis as data collection techniques. E-government is implemented through theintegration of technologies such as the smart water timer for automatedirrigation, the kemandirian.com website for documenting inmate developmentactivities, and an e-commerce application to distribute agricultural productscultivated by inmates to third parties. The analysis uses the six dimensions of theE-GovQual model: ease of use, trust, responsiveness, reliability, content andappearance of information, and citizen support. The system is considered user-friendly, trusted due to its secure data access protocols, adequately responsive ininformation delivery, operationally stable, and informative in terms of content anddisplay. However, interaction features still rely on face-to-face communication,and citizen involvement remains limited and passive. The main supporting factorsinclude strong leadership commitment, the accessibility of the system to both staffand inmates, and the tangible benefits observed in agricultural practices. On theother hand, the inhibiting factors include unstable internet connectivity, lack oftechnical training among staff, and minimal engagement from externalstakeholders. This study concludes that e-government plays a strategic role inaccelerating the digital transformation of inmate development programs but stillrequires improvement in terms of technical infrastructure, human resourcecapacity, and external collaboration to ensure optimal and sustainableimplementation.